Community-Based Sexually Transmitted Infection Screening and Increased Detection of Pharyngeal and Urogenital Chlamydia trachomatis and Neisseria gonorrhoeae Infections in Female Sex Workers in Hong Kong. Issue 4 (April 2015) - Wong, Horas T.H.; Lee, Krystal C.K.; Chan, Denise P.C.
<x xml:space="preserve">Abstract</x> Background Female sex workers (FSWs) are vulnerable to sexually transmitted infections (STIs) and are one of the key populations being infected most by Chlamydia trachomatis and Neisseria gonorrhoeae infections. In Hong Kong, limited data on the burden of chlamydial and gonococcal infections exist because regular screenings are not offered. This study aimed to investigate the prevalence of C. trachomatis and N. gonorrhoeae in FSWs and to assess predictors associated with unprotected fellatio. Methods A cross-sectional study was conduct on 340 FSWs attending a community organization for HIV/STI screening, and a questionnaire addressing sociodemographic and behavioral characteristics was administered to all FSWs. Results The prevalence of syphilis infection was 2.1%, and none was tested positive for HIV. The positivity for pharyngeal C. trachomatis and N. gonorrhoeae was 3.2% and 4.4%, respectively, whereas that for urogenital chlamydial and gonococcal infection was 10.6% and 0.9%, respectively. Of 313 FSWs offering fellatio, having unprotected fellatio with clients was significantly associated with the perceived low risk of contracting STI via fellatio (adjusted odds ratio [OR], 1.88), working in clubs (adjusted OR, 11.14), working on streets (adjusted OR, 3.28), recently started working in the sex industry for 1 year or less (adjusted OR, 3.05), and reporting group sex in the previous year (adjusted OR, 11.03). Conclusions The prevalence of HIV and syphilis infection remains low. This study reveals a relatively high prevalence of N. gonorrhoeae detected mostly in the pharynx. Offering pharyngeal screening for STI would facilitate early diagnosis and treatment of gonococcal infection in FSWs in Hong Kong.